INFORMATION AND EDUCATIONAL TECHNOLOGIES IN TRAINING OF ORGANIC PRODUCTION MANAGERS - Goncharenkо, Nataliia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The article deals with the actual problem of using information and educational technologies in the training of organic production managers. It is established that the development of organic production is important for the diversification of incomes of agricultural enterprises, ensuring the greening of economic activity. The aim of the study is to investigate the theoretical and applied aspects of the use of information technology to train managers in the field of organic production. Despite the fact that Ukraine has the highest rate of increase in the number of producers and retail sales in 2018-2020 in the European countries, the organic sector is significantly behind the European competitors. An important factor hindering the development of organic production in Ukraine is the shortage of skilled workers. It is investigated that decisive factor in the rapid development of organic production in Ukraine is the improvement of professional training of specialists in this field, the provision of human resources, including through the recruitment of young specialists in higher education. It has been found that enhancing IT training is an important area of ​​training for organic production managers, especially in the field of business process automation. It is suggested to use in the educational process of preparation of managers for organic production specialized business simulator "Strategy of green enterprise development". It is based on the economic-mathematical model of optimization of the production program, taking into account the environmental constraints of organic production. The practical use of the Business Strategy Green Business Development Simulator enhances the information and computer training of organic production professionals, gaining the competencies to develop this type of activity and successful professional implementation.